Grief experience among ICU staff with loss of family members during COVID-19 outbreak in IRAN: A qualitative study - Nohesara, Shabnam; Saeidi, Mahdieh; Mosavari, Hesam; Ghalichi, Leila; Alebouyeh, Mahmoud Reza (Frontiers in Psychiatry, 2022)
Introduction The COVID-19 crisis created a lot of problems in people's lives. Different lifestyles, mental health, communication, rituals and traditions, particularly those involved in mourning, have changed drastically. Medical staff faced numerous critically ill patients every day. This greatly distressed the staff, especially the ICU staff. The end result was considerable amounts of mental distress for the medical staff who lost family members to COVID-19 making the distress even more complex. Methods We carried out this qualitative research to study the grief experiences of 12 Iranian ICU staff members at the Rasoul Akram Hospital who had experienced the loss of a family member to the COVID-19 pandemic. We studied the effects of how their own grief experience and how constant exposure to critically ill patients influenced their work with patients. All semi-structured interviews were held in the presence of a faculty member of the psychiatry department of Iran University of Medical Sciences. The interview on the grief experience among ICU staff during the COVID-19 pandemic, consists of 4 issues: Familiarity, Experience during the COVID-19 pandemic, Grieving the loss of a family member and Effects of parallel grief. Results We found five common themes in the result of the experiences of the participants based on content analysis. These consisted of: complex grieving process, new experiences for coping with loss, more empathy for patients, change the meaning of death, and the need for support in work places. Likewise, there were 22 sub themes. Conclusion Paying attention to the details of staff members' life, gender differences, and cultural aspects can give us a better understanding and perception of their grief experiences. This understanding brings out valuable points which can help policy makers pass better laws for the wellbeing of society and people in order to promote leadership in turbulent times.